Health promotion and tobacco control: a transatlantic perspective between Brazil and Portugal - Francisco Lucas de Lima Fontes; Ermelinda do Carmo Valente Caldeira (Revista de Enfermagem da UFPI)
Health promotion, a concept based on the Ottawa Charter, recognizes that health is influenced by economic, social and environmental factors, as well as individual practices. The fight against smoking is one of the most challenging fronts in this context, given its direct relationship with the global burden of chronic diseases and preventable deaths. The articulation of public policies that involve multiple sectors and civil society has proved fundamental in dealing with this problem. In both Brazil and Portugal, health promotion plays a crucial role in integrating tobacco prevention and control actions, reflecting the guidelines of Canada's Population Health Promotion Model.